Protein-only RNase P function in Escherichia coli: viability, processing defects and differences between PRORP isoenzymes. Issue 12 (11th May 2017) - Gößringer, Markus; Lechner, Marcus; Brillante, Nadia; Weber, Christoph; Rossmanith, Walter; Hartmann, Roland K.
Abstract: The RNase P family comprises structurally diverse endoribonucleases ranging from complex ribonucleoproteins to single polypeptides. We show that the organellar ( At PRORP1) and the two nuclear ( At PRORP2, 3) single-polypeptide RNase P isoenzymes from Arabidopsis thaliana confer viability to Escherichia coli cells with a lethal knockdown of its endogenous RNA-based RNase P. RNA-Seq revealed that At PRORP1, compared with bacterial RNase P or At PRORP3, cleaves several precursor tRNAs (pre-tRNAs) aberrantly in E. coli . Aberrant cleavage by At PRORP1 was mainly observed for pre-tRNAs that can form short acceptor-stem extensions involving G:C base pairs, including tRNA Asp (GUC), tRNA Ser (CGA) and tRNA His . However, both At PRORP1 and 3 were defective in processing of E. coli pre-tRNA Sec carrying an acceptor stem expanded by three G:C base pairs. Instead, pre-tRNA Sec was degraded, suggesting that tRNA Sec is dispensable for E. coli under laboratory conditions. At PRORP1, 2 and 3 are also essentially unable to process the primary transcript of 4.5S RNA, a hairpin-like non-tRNA substrate processed by E. coli RNase P, indicating that PRORP enzymes have a narrower, more tRNA-centric substrate spectrum than bacterial RNA-based RNase P enzymes. The cells' viability also suggests that the essential function of the signal recognition particle can be maintained with a 5΄-extended 4.5S RNA.